A Double-Edged Sword? – the Impact of Foreign Accents on Service Communication Outcomes. Issue 8 (17th November 2022) - Yang, Chun; Li, Ruobing
Abstract: To examine the impact of accented service on service communication outcomes, drawing on theoretical framework of stereotypes, a 2 (accent: Indian vs. American) × 2 (product type: stereotype associated vs. no stereotype) online experiment was conducted with 164 participants. Findings suggested that among those who strongly endorsed the positive stereotype associated with the accent, when the stereotype was activated, accented service resulted in favorable perceptions of the service employee and the service. This pattern did not hold for those who held weak beliefs of the positive stereotype. These findings extended the literature on accent and service communication by demonstrating the moderating role of stereotypes, which help explain the inconsistency in the literature. The identified positive impact of accented services also provides practical implications to practitioners.